The effect of multimedia annotation on the vocabulary recall of Grade five pupils - Estandarte, Charmaine Rose T. (MSU Gensan Graduate Education Research Journal, 2016)
This study examined the effectiveness of multimedia annotation on the vocabulary recall of 70 Grade Five pupils of Mariano Villegas Elementary School, Koronadal City. The pupils were divided into two different groups- the experimental group and the control group. The experimental group was exposed to multimedia annotation while the control group was exposed to abstract-text annotation. A quasi-experimental method of research was used in this study. Each group were given a 32-item multiple choice type pre-test and post-test to determine the improvements between and among the groups before and after the interventions were done. At the start of the study, the findings revealed that the Grade Five pupils have poor vocabulary recall. Also, prior to the conduct of the intervention, both groups have more or less the same level of vocabulary recall. Moreover, the results showed that abstract-text and multimedia annotations were both effective. However, multimedia annotation was a better strategy than abstract-text annotation in enriching the pupils' vocabulary recall. Results of the study recommended that multimedia annotation should be utilized in the unlocking of unfamiliar words before reading the passage for the pupils to recall words easily and to be more motivated to learn.